Jim Henson's tale of sand - Henson, Jim 1936-1990; Juhl, Jerry 1938-2005; Pérez, Ramón 1973- (Archaia Entertainment, 2014)
An original graphic novel adaptation of an unproduced, feature-length screenplay follows scruffy everyman Mac, who wakes up in an unfamiliar town and is chased across the desert of the American Southwest by all manners of man and beast of unimaginable proportions
At head of title: Archaia Entertainment and The Jim Henson Company proudly present
Description based on print version record
Keywords: Henson, Jim; Henson, Jim -- Adaptations; Deserts / Comic books, strips, etc; Manuskript; Adaptation; Fantasy comic books, strips, etc; Motion picture plays; Deserts; Motion picture plays -- Adaptations